(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
In order to get consumer attention it is necessary to create creative and innovative packaging designs so that the product remains able to compete closely with its competitors. Being a brand image of a product is becoming an important thing in the midst of today’s business competition. Rahila Brownies is an UMKM that sells products such as cookies, lekker holand, coffee aren, klappertaart, dessert box, and milescrepes. This dedication programme is implemented in every phase of surveys, packaging label design, package design, digital marketing support, follow-up and evaluation. Packaging design is necessary because between variants of Rahila Brownies products is the same so there is no identity or specificity on each type of product. This community service method includes surveys, design, assistance with packaging label design, and assistance with digital marketing. Implementation of digital marketing support activities can contribute to Rahila Brownies to process and develop her business so as to gain brand image and increase her sales. The aspects achieved and targeted in this community service activities are the design aspects of labels and packaging as well as marketing aspects.